The relationship of knowledge and attitudes nurses' compliance in executing early warnings score in hospital royal Prima Medan - Harmocho Kuntoro Hayu Situmorang; Chrismis Novalinda Ginting; Masryna Siagian (Sean Institute, 2024)
Early Warning Score (EWS) can identify patients who are at risk early and uses multiple parameters. The success of patient rescue actions in emergency conditions is very dependent on the responsiveness and accuracy of nurses in carrying out initial assessments via EWS and this really requires cognitive, affective abilities and skills of nurses in solving problems starting with initial identification skills via EWSS. The aim of this research is to determine the relationship between knowledge and attitudes and nurses' compliance in carrying out EWS in the emergency room at Royal Prima Hospital Medan and conducted at Royal Prima Hospital Medan. The population was emergency room nurses at RSU Royal Prima Medan, totaling 26 nurses, sampling used the total sampling method with a total sample of 26 emergency room nurses. The type of research is quantitative with a correlational method with a cross-sectional design. Data analysis uses univariate and bivariate analysis. The results show that the majority of nurses' knowledge and attitudes in carrying out EWS in the emergency room at Royal Prima Hospital Medan are good also show that nurses in carrying out EWS in the emergency room at Royal Prima Hospital Medan have good compliance. In conclusion, there is a relationship between knowledge and attitudes and nurses' compliance in carrying out EWS in the emergency room of RSU Royal Prima Medan, but there is no relationship between education and length of work with nurses' compliance in carrying out early warning scores in the emergency room of RSU Royal Prima Medan, p - value > 0.05.